Pengaruh Minat-Bakat, Sarana-Prasarana dan Motivasi Belajar Terhadap Indeks Prestasi Komulatif Mahasiswa - Novitasari, Dwi; Sanuriza, Irna Il; Triutami, Tabita Wahyu; Wulandari, Nourma Pramestie; Salsabila, Nilza Humaira (Media Pendidikan Matematika, 2020)
This study aims to determine the effect of interests and talents, facilities and learning motivation on students achievement (IPK). The population in this study were students of the Faculty of Mathematics and Natural Sciences and students of the Faculty of Health Science in Universitas Nahdlatul Wathan Mataram, Indonesia. Samples used in this study were 33 students who were taken randomly. Data collection instruments using a questionnaire with a Likert scale that has been tested for validity and reliability before. The collected data were analyzed using multiple linear regression. The results show that: 1) learning facilities and motivation have a significant positive effect on student achievement (IPK), 2) interests and talents have no effect on student achievement (IPK), and 3) interests and talents, facilities and learning motivation simultaneously have an effect on significant on student learning achievement (IPK).